Pancreatic insufficiency as a complication of type 1 diabetes causing enteric hyperoxaluria in a transplant kidney. Issue 7 (4th July 2022) - Chambers, Joshua; Appleton, Alice; Dudley, Christopher
Abstract : A kidney transplant recipient with a medical history of type 1 diabetes mellitus (T1DM) presents to the clinic with an acute kidney injury (AKI) and diarrhoea. Kidney biopsy found deposition of focal oxalate crystals, and further investigation revealed a raised 24-hour urinary oxalate and reduced faecal elastase. Therefore, we present a case of acute oxalate nephropathy (AON) secondary to enteric hyperoxaluria as a result of pancreatic insufficiency caused by T1DM. T1DM is a common cause of end-stage renal failure and exocrine pancreatic insufficiency. Therefore, AON secondary to enteric hyperoxaluria should be considered in patients with a transplant AKI. Earlier testing of 24-hour urinary oxalate and faecal elastase could generate diagnosis before biopsy results and allow commencement of pancreatic replacement therapy earlier to avoid permanent loss of kidney function.